2020
DOI: 10.1017/s1368980020001214
|View full text |Cite
|
Sign up to set email alerts
|

Habitually skipping breakfast is associated with chronic inflammation: a cross-sectional study

Abstract: Objective: We examined whether breakfast frequency was associated with chronic inflammatory, as assessed by high-sensitivity C-reactive protein (CRP) concentration. Design: Cross-sectional study. Setting: Kailuan community, China. Participants: Included were 70 092 Chinese adults without CVD and cancer in 2014 with CRP concentrations <10 mg/l, when breakfast frequency was assessed via a questionnaire, and plasma CRP concentration was measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
1
19
0
1
Order By: Relevance
“…The phenomenon of a later time of first meal consumption may be analogous to breakfast skipping. Compared to always eating breakfast, those never eating breakfast had an increased odds of having a CRP value above 3.0 mg/L of 1.27 (95%CI = 1.15–1.40) [ 55 ]. In a review including 105 peer-reviewed publications, it was concluded that regular breakfast consumption, compared to regularly skipping, improved carbohydrate metabolism and reduced T2DM risk [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of a later time of first meal consumption may be analogous to breakfast skipping. Compared to always eating breakfast, those never eating breakfast had an increased odds of having a CRP value above 3.0 mg/L of 1.27 (95%CI = 1.15–1.40) [ 55 ]. In a review including 105 peer-reviewed publications, it was concluded that regular breakfast consumption, compared to regularly skipping, improved carbohydrate metabolism and reduced T2DM risk [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breakfast is considered the most important meal of the day and affects physical and mental health 18 , 19 . It is reported that breakfast skipping is associated with inflammation, related to an increase in WC and low-density lipoprotein cholesterol, and cardiovascular disease risk 20 23 . We found FGF21 levels to be increased in subjects with a low breakfast consumption frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have found an association of fiber intake with inflammatory biomarkers. [21][22][23] Another possibility is that food timing (eating breakfast) has an impact on chronic inflammation. In a study by Zhu and colleagues, 23 skipping breakfast was associated with higher levels of inflammatory biomarkers (P <.001).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Another possibility is that food timing (eating breakfast) has an impact on chronic inflammation. In a study by Zhu and colleagues, 23 skipping breakfast was associated with higher levels of inflammatory biomarkers (P <.001). Eating breakfast may activate certain pathways that inhibit inflammation.…”
Section: Discussionmentioning
confidence: 99%